2018
DOI: 10.1007/s10103-018-2558-x
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation therapy (PBMT) on acute pain and inflammation in patients who underwent total hip arthroplasty—a randomized, triple-blind, placebo-controlled clinical trial

Abstract: When conservative treatments fail, hip osteoarthritis (OA), a chronic degenerative disease characterized by cartilage wear, progressive joint deformity, and loss of function, can result in the need for a total hip arthroplasty (THA). Surgical procedures induced tissue trauma and incite an immune response. Photobiomodulation therapy (PBMt) using low-level laser therapy (LLLT) and/or light-emitting diode therapy (LEDT) has proven effective in tissue repair by modulating the inflammatory process and promoting pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…Therefore, physical therapies such as ultrasound [24], electrical stimulation [25], exercise [26], spa therapy [27], and low-level laser therapy (LLLT) have been introduced. LLLT is listed as a nonpharmacological and noninvasive treatment option for OA [28], and intensive LLLT offers clinically relevant short-term pain relief for knee OA [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, physical therapies such as ultrasound [24], electrical stimulation [25], exercise [26], spa therapy [27], and low-level laser therapy (LLLT) have been introduced. LLLT is listed as a nonpharmacological and noninvasive treatment option for OA [28], and intensive LLLT offers clinically relevant short-term pain relief for knee OA [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, photobiomodulation (PBM) is widely known for its therapeutic benefits in the protection and regeneration of tissues [18][19][20][21][22][23]. Studies have demonstrated that PBM can reduce pain and inflammation [23][24][25], improve cancer management [26], and stimulate healing and tissue repair [20][21][22][27][28][29][30][31]. PBM is defined by the use of visible light to stimulate biological functions in a non-thermal and non-cytotoxic manner.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of infrared radiation on nerves has been shown in the literature in relation to the photobiological mechanisms of infrared LED, which has an anti‐inflammatory action, such as the modulation of cyclooxygenases and lipoxygenases and the reduction of inflammatory mediators such as prostaglandins, prostacyclins, bradykinin, histamine, substance P, interleukin 1 beta, and tumor necrosis factor alpha, decreasing the activation of the nociceptors . In addition, many studies have shown satisfactory results in relation to the effects of infrared, near‐infrared, or both wavelengths on different pathological conditions such as burn wounds, postsurgery pain, Achilles tendinopathy, hip arthroplasty, knee osteoarthritis, and oral mucositis, where there is an inflammatory process. It is very important to understand whether the chromophores activated by different wavelengths are correlated with the individual responses or eventual cumulative response of both wavelengths in the same treatment.…”
Section: Discussionmentioning
confidence: 99%